2015
DOI: 10.1002/ppsc.201500172
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Rapid Synthesis of Amphibious Yellow Fluorescent Carbon Dots as a Colorimetric Nanosensor for Cr(VI)

Abstract: Amphibious carbon dots (CDs) are prepared by a rapid microwave method; they emit strong yellow emission in H2O, CHCl3, and a polymer matrix. The CDs can be used as a colorimetric nanosensor for the discrimination of Cr(III) and Cr(VI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…When the excitation wavelength progressively increases from 300 to 410 nm, the maximum emission peak is shifted to longer wavelength from 410 to 504 nm. This unique phenomenon of excitation dependent photoluminescence proved that the reaction products must be photoluminescence C-dots, which was also in agreement with optical properties of those C-dots that were synthesized by other research groups 8,10,20,21 . According to De and Karak 27 , the intensity of the PL depends on the number of particles excited at a particular wavelength.…”
Section: Characterization Of C-dotssupporting
confidence: 82%
See 1 more Smart Citation
“…When the excitation wavelength progressively increases from 300 to 410 nm, the maximum emission peak is shifted to longer wavelength from 410 to 504 nm. This unique phenomenon of excitation dependent photoluminescence proved that the reaction products must be photoluminescence C-dots, which was also in agreement with optical properties of those C-dots that were synthesized by other research groups 8,10,20,21 . According to De and Karak 27 , the intensity of the PL depends on the number of particles excited at a particular wavelength.…”
Section: Characterization Of C-dotssupporting
confidence: 82%
“…C-dots are becoming a good alternative for novel fluorescent probes and optical sensors, as a consequence of tunable PL and good biocompatibility 2,3,4 . Recently, C-dots have been demonstrated the use as probes sensitive and selective detection of different ions, such as (Hg 2+ ) 15,16,17 , (Cu 2+ ) 18,19 , (Fe 3+ ) 20 , (Cr 6+ ) 21 , (Be 2+ ) 22 ions. For instance, Liu et al 12 demonstrated the employed of C-dots as probes for sensitive and selective detection of Hg 2+ ions in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is no doubt that the microwave technique could be considered one of the green synthetic methods, and it would play a fundamental role in synthetic chemistry . Moreover, the microwave route has been proved to be a low‐cost and energy‐saving technique for synthesizing CNDs …”
Section: Methodsmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37][38][39] Moreover,t he microwave route has been proved to be al ow-costa nd energy-saving technique forsynthesizingC NDs. [40,41] Herein, we designed ag reen,m icrowave-assisted treatment of p-phenylenediamine (p-PD) for preparing red emissive CNDs. In at ypical synthesis, p-PDc ouldb ec arbonized to form CNDs rapidly by microwavei rradiation in an ethanol/H 2 Os olution (Scheme 1).…”
mentioning
confidence: 99%
“…Compared to the conventional fluorescent nanomaterials (SQDs, metal nanoclusters, and organic fluorescent dyes), CNDs possess numerous superior features including easy preparation and functionalization, no/low toxicity, and high photostability, thus demonstrating a variety of potential applications, such as sensing, biomedicine, catalysis, and optoelectronic devices . To date, many efforts have been done to study the preparations, properties, and applications of CNDs, but most of them show intense emission only in the blue‐light region, and the long‐wavelength (i.e., green‐, yellow‐, to red‐light) emissions are usually very weak . Such a drawback restricts further applications of CNDs, particularly in the biology‐relevant fields because of the common blue autofluorescence of biological matrix and photodamage of biological tissues by ultraviolet excitation light.…”
Section: Introductionmentioning
confidence: 99%